A Qualitative Study of the State of Education during the Corona Virus Epidemic - Sayyad Kheradmand; Maryam Mokhtari; Arman Heydari (توسعه اجتماعی)
After the corona virus epidemic, face-to-face training suddenly gave way to virtual training. Due to the non-availability of facilities, infrastructure and public expectations, a kind of anomic situation arose in the educational system, which has been studied in this research. The present research was conducted using the qualitative method of grounded theory and in-depth interview among 16 teachers of the first secondary level of Yasouj city. Theoretical sampling was used to obtain the samples and continued until the theoretical saturation stage. The method of data analysis was coding based on Glaser and Strauss method. The findings showed that virtual education has become anomic. Because the previous educational order has disappeared and a new order has not replaced it. "Family interaction and education" and "incomplete evaluation" played a role as background and intervening factors in this situation. In anomic virtual education, the teachers' strategy was complacency and the students' strategy was evasion. The consequence of such a situation is the questioning of the teacher's authority, alienation from the educational environment, stereotyping and academic failure of students.